Elastic, load-bearing and autoclavable protein-based graft for coronary revascularization - Sallustio, Federica; El Maachi, Ikram; Andre, Dominic Pascal; Loewen, Alexander; Schmidt, Amanda; Ruetten, Stefan; Heitzer, Marius; Jockenhoevel, Stefan; Rodríguez-Cabello, José Carlos; Fernández-Colino, Alicia (Frontiers in Bioengineering and Biotechnology, 2026)
Autologous grafts, such as the internal mammary artery and saphenous vein, are considered the gold standard for coronary artery bypass. However, there is a critical need for small diameter vascular grafts to meet the demands of coronary artery disease patients, as limitations become especially pronounced due to the extremely small caliber of target vessels. Therefore, we designed and manufactured a miniaturized, autoclavable and synthetic-free vascular graft, composed of elastin-like recombinamers hydrogel and native-like silk fibroin textile to ensure an optimal biological integration and mechanical performance, according to ISO 7198 guideline. The construct demonstrated consistent morphological homogeneity and maintained luminal patency throughout its length. The graft was able to replicate the mechanical performance of the autografts in terms of suture retention and compliance and facilitated the formation of an endothelial monolayer, ensuring a physiologically relevant environment prior to implantation. Moreover, the clinical implantation potential was demonstrated by a successful anastomosis to a human vessel in vitro. The proposed graft represents a viable replacement for this clinical application when autografts are not accessible, avoiding a second surgical site and harvesting morbidity.